2010
DOI: 10.2174/156720110793566290
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery of Minocycline Hydrochloride: A Therapeutic Paradigm in Periodontal Diseases

Abstract: From the literature we can draw conclusions regarding the local use of minocycline in periodontal diseases. This review article attempts to evaluate the role of local delivery of minocycline HCl in the management of periodontal diseases. The efficacies of several local delivery devices of minocycline like minocycline films, strips, gels/ointment, microspheres and nanoparticles are discussed. The functional characteristics of local delivery devices of minocycline, their effectiveness as monotherapy, and compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 66 publications
0
21
0
2
Order By: Relevance
“…Minocycline hydrochloride ointment is a commonly used sustained-release topical antibiotic for periodontitis. 32 Since the microbial flora of peri-implant infection is traditionally associated with periodontitis, 5 minocycline hydrochloride ointment is often used for peri-implant infection. 33 Therefore, after implantation, minocycline hydrochloride ointment was used once a week according to the directions for the positive control group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline hydrochloride ointment is a commonly used sustained-release topical antibiotic for periodontitis. 32 Since the microbial flora of peri-implant infection is traditionally associated with periodontitis, 5 minocycline hydrochloride ointment is often used for peri-implant infection. 33 Therefore, after implantation, minocycline hydrochloride ointment was used once a week according to the directions for the positive control group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria in plaque causes the gums to become inflamed and separate them from the teeth, forming pockets and as the disease progresses, the pockets deepen and more gum tissue and bone are destroyed. In present day world while 75% of the adult population experience at least mild periodontal disease (gingivitis), 20-30% exhibits a severe destructive form of chronic periodontitis (Javed & Kohli, 2010). The periodontal pathogen produces harmful by product and enzymes that break extracellular matrices as well as host cell membranes to produce nutrients for their growth.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, multiple systemic doses of antibiotics have shown several drawbacks, including a rapid decline of the plasma antibiotic concentration to subtherapeutic levels with development of microbial resistance and high peak‐plasma antibiotic concentrations, which may be associated with side effects like hypersensitivity, gastrointestinal intolerance, depression, and tachycardia 6,7 . Some studies also reported poor results because the active product could not achieve an adequate concentration at the site of action where vascularity is compromised and because of the inability of the active product to be retained locally for a sufficient period of time 8‐16 . Thus, the delivery of an active antimicrobial agent directly to the site of infection represents a viable alternative treatment.…”
Section: Methodsmentioning
confidence: 99%